Survival of lung cancer patients in a resource‐limited country. Issue 3 (27th February 2014) - How, Soon Hin; Ng, Teck Han; Kuan, Yeh Chunn; Jamalludin, Abdul Rahman; Fauzi, Abdul Rani
Abstract Aim Data on lung cancer survival are lacking in developing countries. Our objectives were to describe the survival of our lung cancer patients and to determine independent prognostic factors affecting survival. Method All patients diagnosed with lung cancer from August 2007 to August 2010 were recruited from a single referral hospital of the state of Pahang, Malaysia. Detailed demographic data, ECOG (Eastern Cooperation Oncology Group) performance status, stage of disease and treatment were recorded. The date of histology or cytology confirmation was used as the date of entry. Survival time was calculated from the date of entry to the date of death. Results One hundred forty‐nine patients were included for survival analysis. The median age was 62 years and patients were predominantly males (78%) and smokers (78%). The majority had non‐small cell lung cancer (NSCLC) (94%); only six patients (4%) had small cell lung cancer. All patients presented with stage 3 or stage 4 disease. Overall median survival was 18 weeks. "No definitive treatment" and "ECOG 3–4" were the significant independent predictors of death, with the hazard ratios of 2.1 (95% confidence interval [CI] 1.4, 3.0) and 1.6 (95% CI 1.1, 2.3) times, respectively. Among NSCLC patients on treatment, 1‐ and 2‐year survival rates were 27% and 15%, respectively. Conclusion The majority of lung cancer patients in Pahang presented with advanced disease. No definitive treatment and ECOG 3–4 were independent poor prognostic factors.